Chromosome-level and graphic genomes provide insights into metabolism of bioactive metabolites and cold-adaption of Pueraria lobata var. montana. (12th August 2022) - Mo, Changjuan; Wu, Zhengdan; Shang, Xiaohong; Shi, Pingli; Wei, Minghua; Wang, Haiyan; Xiao, Liang; Cao, Sheng; Lu, Liuying; Zeng, Wendan; Yan, Huabing; Kong, Qiusheng
Abstract: Pueraria lobata var. montana ( P. montana ) belongs to the genus Pueraria and originated in Asia. Compared with its sister P. thomsonii, P. montana has stronger growth vigour and cold-adaption but contains less bioactive metabolites such as puerarin. To promote the investigation of metabolic regulation and genetic improvement of Pueraria, the present study reports a chromosome-level genome of P. montana with length of 978.59 Mb and scaffold N50 of 80.18 Mb. Comparative genomics analysis showed that P. montana possesses smaller genome size than that of P. thomsonii owing to less repeat sequences and duplicated genes. A total of 6, 548 and 4, 675 variety-specific gene families were identified in P. montana and P. thomsonii, respectively. The identified variety-specific and expanded/contracted gene families related to biosynthesis of bioactive metabolites and microtubules are likely the causes for the different characteristics of metabolism and cold-adaption of P. montana and P. thomsonii . Moreover, a graphic genome was constructed based on 11 P. montana accessions. Total 92 structural variants were identified and most of which are related to stimulus-response. In conclusion, the chromosome-level and graphic genomes of P. montana will not only facilitate the studies of evolution and metabolic regulation, but also promote the breeding of Pueraria .